The Importance of Digitalization for Sustainable Development of Maritime Industry - Pavlinović, Mira; Račić, Maja; Mišura, Antonija (Transactions on Maritime Science, 2023)
Maritime transport is the driving force of global trade and is one of the fundamental activities of the blue economy. In the face of changes in globalization, it must face technological change. According to the United Nations Conference on Trade and Development, the global commercial shipping fleet grew by 3 percent, in 2020 to 99,800 vessels of 100 gross tons or more. One of the key drivers of technological change in the maritime industry is digitalization. The digitalization of shipping is a step toward making it more environmentally friendly and efficient. This will lead to significant cost savings and improve vessel efficiency, transparency and market access. For the future development of the maritime industry, digitalization combined with environmental sustainability is essential. Experts agree that the COVID -19 pandemic has created certain challenges but also opportunities by creating a great imbalance in the industry and accelerating the progress of digitalization and innovation. The fourth industrial revolution is expected to have a significant impact on maritime transport. The IMO Convention on Facilitation of International Maritime Traffic and the WTO Agreement on Facilitation of International Maritime Traffic have created common standards and regulations that have paved the way for digitalization. Despite the technological advancements in the maritime industry, there is still much room for further research in developing countries. Digitalization in the maritime sector should be promoted as part of global efforts to increase supply chain resilience. It is the pathway to greener and smarter shipping, and this paper aims to provide an insight into the digitalization of shipping and highlight its importance for the future, as well as demonstrate that it contributes to achieving the sustainable development goals. The level of digitalization in seaports and maritime transport will also be analyzed. The adoption of digitalization in the maritime industry is essential and will lead to greener maritime transport, a robust economy and increased safety. The paper includes primary research on the example of shipowners in the coastal liner passenger transport of the Republic of Croatia, and a questionnaire consisting of 19 questions was used to conduct the research.